Suspension culture of human induced pluripotent stem cell-derived intestinal organoids using natural polysaccharides. (September 2022) - Ogawa, Isamu; Onozato, Daichi; Anno, Shiho; Hayashi, Hisato; Kanaki, Tatsuro; Iwao, Takahiro; Matsunaga, Tamihide
Abstract: Currently, there are many challenges in the culture of human induced pluripotent stem (iPS) cell-derived intestinal organoids (HIOs) for use in drug discovery, disease research, and regenerative medicine. For example, the main culture method, embedding culture, makes industrial large-scale culture difficult, and Matrigel, which is used for almost all HIO cultures, is not respected for its application in regenerative medicine. To overcome these challenges, we herein propose a new culture method using low concentrations of natural polysaccharides in a suspension culture. In the present study, five natural polysaccharides free from heterologous animal-derived components were used, and HIOs were successfully cultured in suspension with FP001 and FP003, which are microbial exopolysaccharide analogs of gellan gum. The fabricated HIOs were similar to living intestinal tracts with respect to their gene expression, microstructure, and protein expression. The observed activities of the drug metabolizing enzymes and drug transporters in the generated HIOs suggested that they have pharmacokinetic functions. We believe that suspension culture of HIOs using FP001 or FP003 can be widely applied to not only drug discovery research but also disease research and regenerative medicine. Graphical abstract: Image 1